Effect of cimetidine on cyclophosphamide-induced liver toxicity in albino rats - Adikwu, Elias; Bokolo, Bonsome (Asian Journal of Medical Sciences, 2018)
Background: The clinical use of cyclophosphamide (CP) has been characterised by liver toxicity. Aims and Objectives: This research assessed the effect of cimetidine against CP-induced liver toxicity in a rat model. Material and Methods: Forty eight albino rats divided into 8 groups (A-H) of 6 rats per group gage were used for this study. Group A (control) was administered with water while groups B-D were administered with 5, 10, and 20 mg/kg/day of cimetidine intraperitoneally (ip) for 5 days respectively. Group E was administered with 150 mg/kg of CP ip on the 5th day whereas groups F-H were administered with 5 10, and 20 mg/kg/day of cimetidine for 5 days and CP ip on the 5th day. Rats were subjected to an overnight fast and sacrificed on the sixth day. Serum was extracted from blood and liver function parameters were evaluated. Liver was excised and evaluated for biochemical parameters and histology. Results: CP treatment had no significant (P>0.05) effects on body and liver weights, but significant (P<0.05) increases in alanine aminotransferase, alkaline phosphatase, aspartate aminotransferase, lactate dehydrogenase, gamma, glatamyl transferase, total bilirubin, conjugated bilirubin and malondialdehyde levels were observed when compared to control. Furthermore, significant (P<0.05) decreases in liver superoxide dismutase, catalase, glutathione and glutathione peroxidise were obtained in CP-administered rats when compared to control. The Liver of CP-treated rat shows hepatocyte necrosis around the central veins. However, CP-induced liver damage was significantly (P<0.05; 0.01) ameliorated in a dose-dependent manner in rats administered with cimetidine prior to the administration of CP. Conclusion: Cimetidine ameliorates cyclophosphamide-induced liver toxicity in albino rats. Asian Journal of Medical Sciences Vol.9(5) 2018 50-56